2019
DOI: 10.1038/s41467-019-10366-y
|View full text |Cite
|
Sign up to set email alerts
|

Sequential LASER ART and CRISPR Treatments Eliminate HIV-1 in a Subset of Infected Humanized Mice

Abstract: Elimination of HIV-1 requires clearance and removal of integrated proviral DNA from infected cells and tissues. Here, sequential long-acting slow-effective release antiviral therapy (LASER ART) and CRISPR-Cas9 demonstrate viral clearance in latent infectious reservoirs in HIV-1 infected humanized mice. HIV-1 subgenomic DNA fragments, spanning the long terminal repeats and the Gag gene, are excised in vivo, resulting in elimination of integrated proviral DNA; virus is not detected in blood, lymphoid tissue, bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
225
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(246 citation statements)
references
References 65 publications
3
225
0
5
Order By: Relevance
“…Importantly, CRISPR/Cas9 has now been used to successfully edit HIV-1 in in vitro-infected primary cells and in PBMCs from ART-suppressed individuals [225]. Multiple studies have also shown the successful application of CRISPR-Cas9 in HIV-1 infected humanized mice [226][227][228][229]. These developments culminated in an interesting humanized mouse study showing that the combination CRISPR/Cas9 and a long-acting slow-effective release ART (LASER ART) achieved apparently complete viral clearance in the absence of any detectable Cas9-mediated off-target effects [229].…”
Section: Crisprmentioning
confidence: 99%
“…Importantly, CRISPR/Cas9 has now been used to successfully edit HIV-1 in in vitro-infected primary cells and in PBMCs from ART-suppressed individuals [225]. Multiple studies have also shown the successful application of CRISPR-Cas9 in HIV-1 infected humanized mice [226][227][228][229]. These developments culminated in an interesting humanized mouse study showing that the combination CRISPR/Cas9 and a long-acting slow-effective release ART (LASER ART) achieved apparently complete viral clearance in the absence of any detectable Cas9-mediated off-target effects [229].…”
Section: Crisprmentioning
confidence: 99%
“…A number of combinations have been investigated, such as targeted integration of an antiviral inhibitor-encoding gene into CCR5 locus [252], simultaneous targeting the entry receptor and viral essential genes [253], and combining CRISPR/Cas9-mediated excision of provirus with ART [254]. This, in some way, resembles the principle of ART that uses a cocktail of medications blocking different steps of HIV-1 replication.…”
Section: Hiv-1/aidsmentioning
confidence: 99%
“…Howard Gendelman focused on the potential use of long-acting antiretrovirals as a step towards improving treatment outcomes, highlighting some recent advances (Dash et al, 2019).…”
Section: Long Acting Antiretrovirals Dr Howard Gendelman Universitmentioning
confidence: 99%
“…Howard Gendelman introduced the concept of long-acting slow effective release antiretroviral therapy (LASER-ART) (Dash et al, 2019), that is, hydrophobic lipophilic nanocrystals that serve as agents capable of slowly releasing antiretrovirals prodrugs. The antiretrovirals are modified to improve drug potency, enhance cell membrane permeability, and facilitate encapsulation into nanocrystals that may be rapidly taken up by cells and distributed into the target tissues (Gendelman et al, 2019).…”
Section: Long Acting Antiretrovirals Dr Howard Gendelman Universitmentioning
confidence: 99%
See 1 more Smart Citation